Ruthenium-based structural mimics of [Fe]-hydrogenase - Barik, Chandan Kr (2018)
In this thesis, a series of group VIII metal complexes which are structural mimics of the [Fe]-hydrogenase active site were examined. These were monodentate thiolato complexes of formulae [Ru(2-NHC(O)C5H3NMe)(CO)2(o,o-Me2C6H3S)(L)] (L = MeCN or PMe3), and N,S-bidentate mercaptopyridine complexes of formulae [M(2-NHC(O)C5H4N)(CO)2(2-SC5H4N)] (M = Fe, Ru and Os). Substitution at the 6 and 2,6-position of the pyridine ligand and thiol ligand, respectively, were critical to successful synthesis of the thiolato structural mimics. The mercaptopyridine complexes were found to exist as a mixture of isomers in solution, and the most thermodynamically stable isomer depended on the nature of the metal and the substituent at the 6-position of the pyridine ligand. Preliminary investigations into bioconjugation of a ruthenium-based structural mimic with papain suggested that the ruthenium centre was anchored via the cysteine and imidazole residues of the active site responsible for peptidase activity. The catalytic potential of some of the related complexes was also evaluated. Thus for the group VIII metal complexes [M(2-NHC(O)C5H4N)(CO)2(2-SC5H4N)] (M = Fe, Ru and Os), the iron complex was much more efficient than the ruthenium or osmium analogues as an electrocatalyst in proton reduction. These complexes were also efficient and regioselective catalysts for the cyclisation of α,ω-acetylenic acids to exocyclic enol lactones. The structural mimic precursors [RuBr(2-NHC(O)C5H3NR)(CO)2(MeCN)] (R = H, Me) were also found to catalyze the very rapid hydrolysis of silanes to produce hydrogen gas (TOF ~ 6000 h-1 over 20 s), and showed selectivity for primary over tertiary silanes. Finally, the idea of encapsulation of ruthenium with silica instead of a protein was attempted via hydrolysis and calcination from a molecular single-source precursor, viz., [Ru2(CO)4(μ-2CCH2OSi(OEt)3)2(PPh3)2]. Interestingly, while the silica-encapsulated ruthenium catalyst and the molecular precursor catalysed the formation of cyclopropanes from styrene and ethyl diazoacetate, the product obtained from hydrolysis of the molecular precursor directed the reaction towards a pyrazoline via a [2+3] cycloaddition, the first metal-catalyzed example.